High Glucose Level Impairs Human Mature Bone Marrow Adipocyte Function Through Increased ROS Production - Rharass, Tareck; Lucas, Stéphanie (Frontiers in Endocrinology, 2019)
Bone marrow adipocytes (BMAds) accumulate in aging, menopause, and metabolic diseases such as Type 2 diabetes. These osteoporotic conditions are associated with oxidative stress and hyperglycemia which are both considered as critical factors underlying bone fragility. Glucose excess and reactive oxygen species (ROS) are known to favor adipogenesis over osteoblastogenesis. In this study, we investigated whether high glucose exposure could determine dysfunction of mature BMAds, specifically through ROS production. The effects of low (LG, 5 mM) or high glucose (HG, 25 mM) concentrations were examined using human bone mesenchymal stromal cells (hBMSCs) in the time course of differentiation, and, up to 21 days once adipocytes were mature. HG did not alter the adipocyte differentiation process of hBMSCs. Yet, after 21 days under HG exposure, PPARG, CEBPA, and adiponectin mRNA expressions were decreased. These alterations were also observed following adipogenic inducer withdrawal as well as in adipocytes fully differentiated in LG then cultured in HG for the last 11 days. Without inducers, HG condition also led to decreased leptin mRNA level. Importantly, intracellular and extracellular ROS concentrations measured using Amplex Red were significantly raised by 50% under HG exposure. This rise was observed once adipocytes ended differentiation and was reproduced within the different cell culture settings without any cytotoxicity. Among genes involved in ROS metabolism, the mRNA level of the H2O2 generating enzyme NOX4 was found upregulated in the presence of HG. Following cell separation, mature BMAds were shown to overproduce ROS and to display the gene alterations in contrast to non-lipid-laden cells. Finally, a non-lethal treatment with a pro-oxidant agent under LG condition reduces the mRNA levels of PPARG, adiponectin, and leptin as the HG condition does in the absence of inducers, and amplifies the effect of glucose excess on gene expression. HG concentration drives mature BMAds toward altered expression of the main adipokines and transcriptional factors. These perturbations are associated with a rise in ROS generation likely mediated through enhanced expression of NOX4. Mature BMAds are thus responsive to changes in glucose and ROS concentrations, which is relevant regarding with their phenotype and function in age- or metabolic disease-related osteoporosis.